1991
DOI: 10.1128/jvi.65.5.2761-2765.1991
|View full text |Cite
|
Sign up to set email alerts
|

Live attenuated pseudorabies virus expressing envelope glycoprotein E1 of hog cholera virus protects swine against both pseudorabies and hog cholera

Abstract: To investigate whether live attenuated pseudorabies virus (PRV) can be used as a vaccine vector, PRV recombinants that expressed envelope glycoprotein El of hog cholera virus (HCV) were generated. Pigs inoculated with these recombinants developed high levels of neutralizing antibodies against PRV and HCV and were protected against both pseudorabies and hog cholera (classical swine fever).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(54 citation statements)
references
References 28 publications
1
51
0
2
Order By: Relevance
“…For instance, pigs that were immunized with recombinant virus expressing CSFV E0 or E2 protein were protected against CSFV challenge (47). In some cases, immunization of animals with recombinant virus expressing other CSFV proteins failed to induce detectable neutralizing antibodies, whereas the animals were protected against lethal CSFV infection, which indicated that virus-specific T lymphocytes participated in a protective immune response against CSFV (38,44,48). Currently, cellular immune responses, especially production of virus-specific cytotoxic T lymphocytes (CTL), are receiving more attention for their potential roles in developing efficient epitope vaccines against CSFV (18,35).…”
mentioning
confidence: 99%
“…For instance, pigs that were immunized with recombinant virus expressing CSFV E0 or E2 protein were protected against CSFV challenge (47). In some cases, immunization of animals with recombinant virus expressing other CSFV proteins failed to induce detectable neutralizing antibodies, whereas the animals were protected against lethal CSFV infection, which indicated that virus-specific T lymphocytes participated in a protective immune response against CSFV (38,44,48). Currently, cellular immune responses, especially production of virus-specific cytotoxic T lymphocytes (CTL), are receiving more attention for their potential roles in developing efficient epitope vaccines against CSFV (18,35).…”
mentioning
confidence: 99%
“…Outside the EU, CSFV vaccination of domestic pigs is widely practised using a live C-strain vaccine as well as a bio-tech CSFV E2 glycoprotein subunit marker vaccine [64,59,65]. The application of bio-tech techniques for the development of experimental or commercial vaccines includes the use of E2 subunit marker vaccines expressed in baculo virus [66], E2 subunit vaccine [67], a chimeric BVDV-CSFV marker vaccine [68], and recombinant PRV expressing CSFV glycoprotein that has been shown to be protective for diseases due to PRV and CSFV [69].…”
Section: Classical Swine Fevermentioning
confidence: 99%
“…As mentioned above, PRV was one of the first animal herpesvirus suggested to be suitable as bivalent vaccine vector. Proof of concept was achieved by showing that attenuated PRV expressing envelope glycoprotein E2 of classical swine fever virus constitutes an efficacious, safe and non-transmissible vaccine against both Aujeszky's disease and classical swine fever [108]. Despite the promising results, this vaccine was never commercialised.…”
Section: Herpesvirusmentioning
confidence: 99%